New records of Hypoxylon (Ascomycota, Hypoxylaceae) for the Argentine Yungas - Diaz, Sofía M. (2018)
Hypoxylon aeruginosum var. aeruginosum, H. fendleri and H. undulatum collected in the subtropical montane forest from northwest Argentina are reported for the first time for the Southern Cone. We describe and analyze their teleomorph and anamorph, and provide photographs and drawings of the most relevant structures. Moreover, a key to Hypoxylon species so far known from Argentina is given.